Biofortification of crops with micronutrients through agricultural approaches - Sharma, Sushil K; Sharma, Mahaveer P; Ramesh, Aketi (Indian Farming, 2015)
In developing countries, due to access to foods deficient in micronutrients, micronutrient malnutrition in human population is widespread. Traditional strategies to supply micronutrients to susceptible populations have relied on supplementation or food fortification programmes. Unfortunately, these interventions have not always been successful. An alternative low cost and eco-friendly solution is to increase micronutrient concentration in the edible portion of crops. Currently, it is being achieved by plant breeding and agronomic agricultural management practices and thereby helps combating malnutrition in resource-poor people living in developing countries including India. Advocating the application of microorganisms is a potential, emerging short term option to enrich food grains with micronutrients.